2017
DOI: 10.1108/ijpsm-10-2016-0160
|View full text |Cite
|
Sign up to set email alerts
|

Public procurement policy for small and medium enterprises in developing countries

Abstract: Purpose Increasing the share of small and medium enterprises (SMEs) in public procurement through targeted support policies is often fraught with organisational and institutional challenges as can be seen from the experiences of many developed countries. This has profound implications for emulating such policies in developing countries where administrative capacities may be low for efficient policy management. The purpose of this paper is to widen the canvass of SME procurement policy discourse by exploring a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
12
0
4
Order By: Relevance
“…Notwithstanding the presence of some SPP requirements, they are discretionarily enforced and complied with based on the financial and technical capacity of the procurement entities, suppliers' ability to respond to SPP, and local capacity for subcontracting amid other normative factors by political executives. Similarly, in a more recent discussion on SMEs, Patil () found that a public procurement policy meant to increase local participation in India is hampered by weak administrative capacity and unfavourable risk‐averseness measures by public authorities, which he termed as “efficiency syndrome” (p. 402). It is therefore plausible to suggest that developing countries lack capacity for SPP.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notwithstanding the presence of some SPP requirements, they are discretionarily enforced and complied with based on the financial and technical capacity of the procurement entities, suppliers' ability to respond to SPP, and local capacity for subcontracting amid other normative factors by political executives. Similarly, in a more recent discussion on SMEs, Patil () found that a public procurement policy meant to increase local participation in India is hampered by weak administrative capacity and unfavourable risk‐averseness measures by public authorities, which he termed as “efficiency syndrome” (p. 402). It is therefore plausible to suggest that developing countries lack capacity for SPP.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In addition to lack of clear SPP legal framework, Table shows that entities including those responsible for enforcing SPP standards lack the requisite capacity to design SPP criteria and to evaluate suppliers. This is no different in the SME public procurement policy in India (Patil, ). SPP practice involves several national stakeholders: the procurement entities and their bureaucrats, members of the tender evaluation committees at the various sectors, suppliers, regulatory and standardisation institutions, and citizens and political executives (policymakers).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Public procurement can be used to achieve social, economic and technological objectives (Ribeiro, Júnior, Raun, & Li, , p. 4), to promote small and medium business in developing countries (Patil, , p. 391) or even enforce sustainability, as analysed by Aragão and Jabbour (). It refers to the acquisition of goods or contracting services by the public administration (Sorte Junior, , p. 30), which are ultimately used to provide some service to the population.…”
Section: Introductionmentioning
confidence: 99%